Investigating the Effect of Inclination Angle of Magnetic Field Vector on Silicon PV Modules - Dioari Ulrich Combari; Emmanuel Wendsongré Ramde; Bruno Korgo; Ramatou Saré; Martial Zoungrana; Issa Zerbo (International Journal of Photoenergy)
In earlier studies, we have shown theoretically and experimentally that magnetic fields (MFs) have negative impact on silicon PV module (photovoltaic module). A noticeable decline in photocurrent with a slight increase in photovoltage was observed. Also, how those fields affected other key module’s parameters was also studied. These studies concluded that an increase in the magnitude of the MF resulted in the decrease of the efficiency of the silicon PV module. The previous experimental studies assumed that the MF vector formed zero angle of inclination with respect to the photosensitive face of the module. They did not factor in any effect that could be observed when the field vector is inclined. The present experimental work is an attempt to fill that gap. The characteristic curves of the PV module were plotted in the same system of axis for different values of the inclination angle of the MF vector. Correspondingly, the characteristic values (Pmax, Imax, Vmax, Isc, and Voc) of the PV module were also determined. These parameters then allowed the calculation of the efficiency of the module, its fill factor, and the equivalent circuit series and shunt resistances. It is observed that the module efficiency increases with the inclination of the MF vector, indicating that the effect of the MF on the PV module is reduced when its vector aligns towards a direction that is perpendicular to the base of the module. For example, when α moves from 0 to 90°, the power output and consequently the efficiency of the PV module relatively increase of 14%.